FOREIGN POLICY OF NARENDRA MODI, DEMOCRACY SUPPORT AND SOUTH ASIA - SANDEEP E (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The article attempts to identify the importance of democracy promotion in India’s foreign policy towards South Asian countries during the Narendra Modi government (2014 May-2019 May). The major aim is to analyse what happened to the journey with a new attention to democracy promotion, after decades of disregard and reluctance, commenced by Vajpayee government and Manmohan government, under the regime of Narendra Modi. It will attempt to locate both continuities and departures at policy level as well as at implementation level. As part of this, the foreign policy approach towards South Asian countries except Pakistan will be discussed here. the study reaches to a point that the democracy promotion policy of Prime Minister Narendra Modi reflects more continuity than any notable departures.